The histopathological predictor factors in the recurrence of cervical carcinoma stage IB - IIA after radical hysterectomy (Faculty of Medicine Universitas Indonesia, 2001)
The aim of this study is to know the incidence of cervical carcinoma stage IB - IIA recurrence after radical hysterectomy and the histopathologic factors which are related to it. This was a retrospective cohort study involving 68 patients with recurrence cervical carcinoma stage IB - IIA who underwent radical hysterectomy, However, there were only 58 cases which fulfilled the study citeria, and therefore were evaluated histopathologically. The histopathologic evaluation consisted of differentiation, inflammatory reaction, lymph-vascular permeation, invasion to the vagina incision margin, and to endometrium, lymph nodes metastasis, and the depth of stromal invasion. The incidence of the cervical carcinoma stage IB-IIA recurrence 2 years after radical hysterectomy was 30.8% (21 out of 68 cases). The recurrence occurred in nine (75%) out of 12 cases with lymph node metastasis, compared to 10 (21.7%) out of 46 cases without lymph node metastasis (P = 0.0004). In addition, eight out of 11 adenosquamous carcinoma cases had recurrence (p = 0.01). There was only one out of the 12 cases with the depth of stromal invasion of < 5 mm that had recurrence compared to 18 out ofÂ 45 cases with stromal invasion of > 5 mm (P = 0.02). The clinical factors such as parity, staging, size of the tumor were not statistically significant. The other pathologic factors such as differentiation, inflammatory reaction, and parametrial, vagina incision margin and endometrial invasion were not statistically signifcant. The incidence of the recurrence of cervical carcinoma within 2 years after hysterectomy was related to the pathological risk factors i.e. lymph node metastasis, adenosquamous cell carcinoma andÂ the depth of stromal invasion. (Med J Indones 2001; 10: 79-83) Keyword: risk factor, cervical cancer